Synthesis of C-glycosyl triazolyl quinoline-based fluorescent sensors for the detection of mercury ions. (4th October 2016) - Wang, Linfang; Jin, Jianzhong; Zhao, Linwei; Shen, Hongyun; Shen, Chao; Zhang, Pengfei
Abstract: A series of novel C -glycosyl triazolyl quinoline-based fluorescent sensors have been synthesized via click chemistry. It was found that novel sensors exhibited good selectivity for Hg 2+ over many other metal ions. The glucose framework was introduced to increase the water-solubility of the fluorescent sensors and broaden its application for the detection of Hg(II) in the water-solubility biological systems. The mechanism of the chemodosimetric behavior of the sensors has been attributed to a binding mode of triazolyl quinoline with Hg 2+ which has been characterized by a number of spectroscopic techniques. Graphical abstract: Highlights: A new type of C -glycosyl triazolyl quinoline derived from D-glucose was synthesized via click chemistry. The novel sensors exhibited good selectivity for Hg 2+ over many other metal ions. The glucose framework was introduced to increase the water-solubility in biological systems.